QS. Al-Alaq (3) : Landasan Berpikir Kritis sebagai Kunci Inovasi - Ratnaduhita Nabilah Azzahra; Renaningtyas Putri Lestari; Wayan Mayuda (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
In the digital era and the Industrial Revolution 4.0 towards Society 5.0, innovation becomes crucial, but many young people are still trapped in consuming information immediately without sufficient analytical skills. The absence of a culture of literacy and reading causes innovation that is only based on imitation. The initial message of Islam